Effects of Holding Temperature on Bainite Transformation in Cr-Mo Steel - M. Sarizam; Y. Komizo (Journal of Mechanical Engineering and Sciences, 2014)
The effect of holding temperature on the variant selection mechanism during bainite transformation was investigated in 2Cr-1Mo steel. The transformation behaviour was studied by using high temperature laser scanning confocal microscopy (LSCM) via in situ observation. The specimen was heat treated to 1350 °C and was held for 60 s before being cooled to 560 °C and 580°C. In both conditions, each specimen was isothermally transformed for 1 hour and cooled to room temperature. The heat-treated specimen was then analysed using the electron backscattered diffraction (EBSD) method. As a result, variant preferential selection is more prominent at a higher holding temperature, which coarsened the block and packet boundary and is connected with a low misorientation angle variant.